Validation of the Big Five Questionnaire (BFQ-C), short version, in colombian adolescents (2022)
Introduction. The most widely accepted theoretical and measurement model in personality study is the Big Five Personality Test, designed to measure five traits: Extraversion, Agreeableness, Conscientiousness, Neuroticism, and Openness. One of the most commonly used instruments for evaluating personality in children and adolescents is the BFQ-C. However, its applicability may be limited by its length. The short version of the test has shown stability across different cultures but there is no empirical evidence on its psychometric properties to enable it to be used in the Latin American context. Objective. This study seeks to validate the short version of the Big Five Questionnaire for Children (BFQ-C) in the Colombian population. Method. The questionnaire was administered to 844 adolescents (55% boys and 45% girls) aged between 11 and 16 (M = 13.55 and SD = 2.30). Seven possible models were obtained from a series of exploratory and confirmatory analyses to explain the factorial structure of the test, which were compared with each other to find the model with the best statistical fit. Results. The model with the best absolute fit coincided with the five-factor proposal of the scale, for which empirical evidence is provided for the universality of the Big Five model. The factors showed adequate levels of reliability. Discussion and conclusion. The short version of the BFQ-C has good psychometric properties in adolescents and constitutes a useful instrument for measuring personality in the Latin American context.